ANEMIA DEVELOPING IN VIRAL HEPATITIS B AND C - Ahmedova , N.Sh.; Nurullaeva, D.F. (Educational Research in Universal Sciences, 2023)
The prevalence and steady growth of liver diseases among the population is one of the urgent and serious problems of modern medicine. Hepatitis V and C viruses are one of the most common parenterally transmitted infections today and remain the main cause of chronic liver diseases. Hepatitis is widespread in the working class of the population, that is, among people aged 30 to 50 years, especially among men more often than women, the infection is chronic in about 80% of patients, and the rate of development of liver disease in 15-20% of cases passes to the terminal stage in an average of 20 years. , moreover, the fact that chronic hepatitis occurs with clinical symptoms other than the liver means that this disease is not only a medical but also an important economic and social problem.